Literacy teachers in Madrid province through «Catastro de Ensenada» (1749-1756) - González Barrero, Nuria (Historia y Memoria de la Educación, 2015)
This paper aims to offer a glimpse into the real situation of literacy teachers, and to a lesser extent, grammar teachers, in the province of Madrid in the 18th century, based on relevant information gathered from «Libros de Estados Generales» of «Catastro de Ensenada» (1749-1756). First, we analyze the distribution of literacy teachers in cities and villages in the Madrid area, their wages, the supplementary jobs they had apart from teaching, and how they were valued socially. We also compare their job to other types of professions in order to get a more accurate idea of their conditions and real situation in the mid-eighties. Similarly, we make a comparison of literacy teachers’ and grammar teachers’ socio-economic circumstances in the province of Madrid with that of teachers in other Spanish provinces where the «Catastro de Ensenada» was also conducted.